Wind Energy in Colombia : A Framework for Market Entry - Vergara, Walter; Deeb, Alejandro; Toba, Natsuko; Cramton, Peter; Leino, Irene (World Bank, 2012)
The purpose of this report is to provide decision makers in Colombia (and by extension other countries or regions), who are considering the deployment or consolidation of wind power, with a set of options to promote its use. The options presented are the result of an analysis of the Colombian market; this analysis included simulations and modeling of the country's power sector, and extensive consultations with operators, managers, and agents. More information on the analysis and simulations is presented in the appendixes. Wind was chosen to exemplify the range of renewable energy alternatives available to complement traditional power sector technologies on the basis of its technical maturity, its relatively low cost compared to other options, the country's experience, and its wind power potential. This report constitutes the second phase of a barrier analysis to wind energy in Colombia.